Mencegah Tindakan Pungli (Pungutan Liar) di Sekolah: Penelitian - Sali Imaduddin; Ismail; Doni Martin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Pungli stands for illegal levies, which is the act of requesting or receiving a sum of money or goods from the public by state officials or state administrators that are not in accordance with the provisions of laws and regulations. Extortion is a form of abuse of authority and can be categorized as an act of corruption. Illegal collection or extortion is the practice of asking for payment that is not in accordance with regulations, often considered as extortion, fraud, or corruption. Factors that influence corruption include abuse of authority, mental aspects, economics, organizational culture, limited human resources, and weak supervision. Illegal fees are clearly regulated in the Criminal Code, but extortion, fraud, and illegal fees are interrelated criminal offenses. This research discusses extortion in schools, including its definition, causative factors, impact, and eradication strategies. It also discusses the roles and responsibilities of service implementers, supervisors, and the community in overcoming extortion in schools. Thus, this research hopes to understand more about extortion in schools and how we can address this issue to improve the quality of education and honesty in schools.